2015
DOI: 10.1017/s0022215115001632
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural hearing loss following induction chemotherapy plus concurrent chemoradiotherapy for advanced nasopharyngeal carcinoma

Abstract: The docetaxel, cisplatin and 5-fluorouracil induction chemotherapy regimen followed by concurrent chemoradiotherapy was associated with a lower incidence of sensorineural hearing loss than conventional concurrent chemoradiotherapy. This regimen may be the preferred choice of treatment for hearing preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A total of 994 non-duplicate citations were identified by using the selected keywords. After the final review, 66 articles were eligible for inclusion in this study [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] . The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 994 non-duplicate citations were identified by using the selected keywords. After the final review, 66 articles were eligible for inclusion in this study [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] . The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our modeling, the occurrence of neurosensorial hearing loss was set for the majority of patients with NPC (including all T2-4N0-3 diseases) who should receive cisplatin-based concurrent chemotherapy as a part of their radical treatment. The use of cisplatin may also induce an irreversible ototoxicity, thereby increasing the absolute risk of irradiationrelated hearing loss 29,[32][33][34] ; however, the use or nonuse of cisplatin would not affect our evaluation for the benefits of IMPT over IMRT in reducing the neurosensorial hearing loss. Second, the HSUVs applied for "dysphagia and hearing loss," "xerostomia and hearing loss," and "dysphagia, xerostomia and hearing loss" (0.579, 0.622, and 0.539) in our study were the lower limit values derived from the established HSUVs for "dysphagia," "xerostomia," "hearing loss," "dysphagia and xerostomia."…”
Section: Discussionmentioning
confidence: 99%
“…7,9 In the Markov model of IMRT strategy, the occurrences of dysphagia and xerostomia were set according to the longterm follow-up results reported by Huang et al, in which the incidences of dysphagia and xerostomia (≥grade 2) after IMRT were 0.22 and 0.34, respectively 12 ; and the incidence of high-frequency sensorineural hearing loss was set as 0.35 from the 1st to the 3rd year to simulate the plateau, which then increased with a same annual rate in the following 10 years until it reached to the maximum incidence of 0.446 in the 13st year. 29,[32][33][34] Based on the above setups for late toxicities in the IMRT strategy, the late toxicities probabilities in the IMPT strategy were calibrated to measure up to a preset NTCP-reduction level (e.g., 10%, 20%, 30%, 40%, 50%, or 60%). Initially, we assumed that IMPT could provide an NTCP reduction of 30% in dysphagia, xerostomia, and sensorineural hearing loss for the base case.…”
Section: Setups For Base Casementioning
confidence: 99%